Synthesis of Polypyrrole Coated SnO2-ZnO Electrospun Nanofibers via Vapor Phase Polymerization Method - H. A. Khorami; M. Keyanpour-Rad; A. Eghbali; M. R. Vaezi (Journal of Nanostructures, 2012)
This paper reports the synthesis of polypyrrole coated SnO2/ZnOelectrospunnanofibers via vapor phase polymerization method. In order to prepare one dimensional (SnO2- ZnO)/polypyrrole with the core sheath structure, first SnO2-ZnO composite nanofibers were synthesized via electrospinning method followed by adsorption of Fe 3+  on the surface of the SnO2-ZnO nanofibers and finally pyrrole was polymerized on the surface of the fibers. The results of simultaneous thermal analysis (STA), X- ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) of the nanofibers confirmed the success of synthesis of (SnO2-ZnO)/polypyrrole core sheath compound.